Study for the Effect on Structure and Properties of Highland Barley Proteins During Stir-frying - HUANG Liang-liang; JIANG Kang-hui; LI Qi; YANG Jie; HU Yun; LI Liang (Liang you shipin ke-ji, 2025)
To investigate the effect of frying on the protein structure and properties of highland barley, the proteins extracted from highland barley before and after frying were analyzed using SDS-PAGE electrophoresis, Fourier transform infrared spectroscopy, ultraviolet spectroscopy, endogenous fluorescence spectroscopy, X-ray diffraction, chemical bonding, microstructure and rheological property analyses. The results suggested that some subunits of proteins in the fried highland barley were degraded to the small-molecular-weight polypeptides or oligopeptides. In the secondary structure, the α-helix structure contents increased by 2.41% and 2.26%, respectively, whereas the β-folded structure contents decreased by 1.74% and 3.55%, respectively, and the random coil content showed little change. The absorbance strength of ultraviolet absorption spectrum was enhanced, the fluorescence intensity of endogenous fluorescence spectrum decreased, and the maximum emission wavelength was red shifted. After frying, the protein free sulfhydryl group and disulfide bond in both black and white highland barley were significantly changed (P < 0.05), which increased by 0.04 μmol/g, 0.43 μmol/g, 0.23 μmol/g and 0.31 μmol/g, respectively. As discovered from microstructure analysis, the protein surface of the fried highland barley was rougher, more uneven and the molecules were more closely connected. The trends of G' and G" values of the protein solution were consistent before and after frying; besides, with the increase in angular frequency, the tan δ value was gradually greater than 1, and the internal microstructure of the protein solution changes at high angular frequency, which may resulted in phase transition and exhibit good viscosity. In summary, frying can change the protein structure of highland barley, and partially alter the properties.